University Climate Affecting the Teachers’ Motivation Towards Improvement of Teachers’ Classroom Performance in Shandong Qilu University of Technology - Guo, Yanling (Pacific International Journal, 2024)
This study examined how university climate impacts teacher motivation at Qilu University of Technology in China. Motivation theories highlight drives to satisfy needs and internal cognitions. University climate factors like supportive leadership, collegial relationships, professional development, and adequate resources are found to enhance teacher motivation. However, climate-motivation links are understudied in China’s centralized education context. This correlational study surveyed 168 faculty on their perceptions of university climate dimensions (leadership support, collegial relationships, professional development, resources) and motivation levels (intrinsic - achievement, relationships, autonomy; extrinsic - compensation, security, reputation, pressure) using researcher-developed questionnaires. Data analysis determined profile, climate and motivation levels, differences based on demographics, and their relationships using descriptive and inferential statistics. Results revealed moderately positive climate perceptions, with peer support viewed most favorably. Motivation was consistently high, especially intrinsic motivation. All climate dimensions positively correlated with motivation, particularly intrinsic motivation. A supportive climate fulfilling needs was significantly associated with heightened motivation. Findings imply administrators should strengthen leadership, peer collaboration, professional development and resources to enhance teacher motivation and performance.